Por uma ética da falta: abertura à repetição diferencial - Rocha, Isabela Fontes (2023)
The path outlined in this dissertation, based on the four fundamental concepts listed by Lacan in Seminar, Book 11, addresses the theme of the ethics of psychoanalysis, the clinical context, and the samples extracted in analysis as laws that permeate desire. The research consists of a literature review that describes the theoretical path traced by Lacan in Seminar, Book 07, with the aim of bridging the field of ethics with the field of morbid lack represented in the concept of the object a. This endeavor begins with the ethical issues inherent in the fundamental concepts, encompasses the process of subject formation, and ends with the reflections that the moral field assumes the presentification of the Real as such. The work draws on myths to reveal the constitutive division and impasses of becoming a subject in a field that belongs to the Other and, therefore, is lacking. The morbid lack causes attraction and horror to the subject and also drives them to search for the lost object, das Ding. It is possible to observe that the law, which arises as the effect of the object a, will be a trait that repeats itself like a malign fate, that is, a ghost that shapes everything from the fantasies of the absolute Other to the impasses of desire. The research notes the field of impossibility in which ethics is inserted, since any vicissitude of the drive will leave the inherent discomfort of the death drive. It can be inferred that psychoanalysis provides a subjective destitution that results in a subject warned of the limits of the Symbolic, the aggressiveness of the Imaginary, and the anguish of the Real, and that its ethics, despite being based on the impossible, that is, on what cannot be denied, allows for the opening for each subject to invent a singular form of differential repetition.